PELAKSANAAN PENCEGAHAN TINDAK PIDANA KORUPSI OLEH KOMISI PEMBERANTASAN KORUPSI DI INDONESIA - Halim, Azimu; Efendi, Erdianto; Indra, Mexsasai (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Corruption is a serious problem that is being faced in Indonesia, particularlythe province of Riau. In law enforcement is not only necessary enforcement action butalso preventive measures. Therefore, corruption must be addressed in a rational way.One rational business is to do prevention. The purpose of this study, for to know theimplementation of prevention of corruption by the Corruption EradicationCommission in Indonesia, to know the constraints prevention of corruption by theCorruption Eradication Commission in Indonesia and to determine the prevention ofcorruption by the Corruption Eradication Commission in Indonesia. This type ofresearch is a sociological law research, because in this study the authors directlyconduct research on locations or places studied in order to give a complete and clearpicture of the problems examined. This research was conducted at the CorruptionEradication Commission of the Republic of Indonesia, the Directorate of SpecialCriminal Regional Police Riau and Riau High Court, while the sample population isa whole party with regard to the problems examined in this penelitiaan, data sourceused, primary data, secondary data and data tertiary, data collection techniques inthis study with interviews and literature study. Prevention of corruption has not beenrun up by the presence of obstacles such as budget and human resources. Efforts toovercome this obstacle is to increase the budget, build quality human resources,building a bureaucratic assessment system and promote the dangers of corruption tothe public. Parties to the Corruption Eradication Commission in implementing theprevention of criminal acts of corruption further strengthen coordination in carryingout functions with other agencies, as well as find solutions to the obstaclesencountered and maximize socialization for prevention.Keywords : Prevention - Criminal Act - Corruption